Job Search, Unemployment Protection and Informal Work in Advanced Economies - Iain W. Long; Vito Polito (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper investigates the incentives that may induce workers to supplement income from unemployment benefits by engaging in temporary informal work. Using a dynamic model of job-search with moral hazard that incorporates a stylised schedule of benefit payments, we describe how informal sector participation changes over the duration of unemployment, in turn affecting the incentive to search for formal employment. We find that increasing benefit generosity makes job seekers less reliant on informal work, enabling them to search more intensively. At the same time, when detection rates are low, informal work participation may decline as benefit exhaustion approaches, reinforcing this effect. From a policy perspective, the analysis identifies scope for reallocation of resources towards less generous programmes within unemployment protection, which would reduce the size of the informal sector and unemployment in the economy.
Keywords: J46; J64; J65; K42; 330; job-search; informal sector; unemployment insurance; moral hazard